Iliorenal periscope graft to maintain blood flow to accessory renal artery - Murat Canyigit; Mete Hidiroglu; Emrah Uguz; Huseyin Cetin (Diagnostic and Interventional Radiology, 2015)

(untitled)
Parallel endografts such as “chimney” and “periscope” are being increasingly used to maintain blood flow to visceral and supra-aortic branches in patients with different aortic disorders. We present a new technique, “iliorenal periscope graft”, in a patient with abdominal aortic aneurysm undergoing endovascular aortic repair. In this case, left accessory renal artery flows were provided by an iliorenal periscope graft that extends from the left accessory renal artery to the right common iliac artery in a retrograde fashion.